2014
DOI: 10.1016/j.ihj.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic prevalence and pattern of coronary artery disease in women

Abstract: There has been a change with regard to clinical presentation and onset of risk factors for CAD at young age, but the load of atherosclerotic burden and pattern of involvement of coronary arteries have not changed in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 9 publications
7
16
0
2
Order By: Relevance
“…According to certain research, close associations exists between traditional risk factors and the risk of CAD in young adults [5,13]. Based on the results of the current study, MI was higher in ≥45 years group.…”
Section: Discussionsupporting
confidence: 61%
“…According to certain research, close associations exists between traditional risk factors and the risk of CAD in young adults [5,13]. Based on the results of the current study, MI was higher in ≥45 years group.…”
Section: Discussionsupporting
confidence: 61%
“…In Nurses' health study in USA, the age adjusted relative risk for non-fatal myocardial infarction and fatal CAD among female with a parental history of acute Myocardial infarction before age 60 years were 2.8 and 5.0 respectively indicated age as risk factor for CAD [22]. The prevalence of CAD in our study population was 55.2% compared to 44.8% with normal coronaries, our findings come in according with a study found in India among 500 subject in 2013 with similar study population reported a prevalence of obstructive CAD 55.8% and normal coronaries 44.2% [23]. Traditional cardiac risk factors are highly prevalent in women.…”
Section: Discussionsupporting
confidence: 81%
“…18 Another study by Ezhumalai et al also reported higher prevalence of diabetes and dyslipidemia in old age females as compared to the younger ones. 19 Kher et al conducted a comparative study between young male and female patients to study the risk factor profile and type of CAD. The authors found higher prevalence of hypertension and diabetes in young females as compared to the young males.…”
Section: Discussionmentioning
confidence: 99%
“…Ezhumalai et al found higher incidence of DVD (19.7% versus 15.2%) and TVD (16.5% versus 7.8%) in old age females as compared to the young age females. 19 The VIRGO study emphasized on the importance of risk identification, and education of young females at all levels of health care management systems. 21 Since the risk profile is different in young females, so there is a need to re-evaluate the diagnostic and management options in these patients with early implementation of preventive strategies to prevent the occurrence of CAD in these patients.…”
Section: Discussionmentioning
confidence: 99%